In silico Molecular Docking of Cyclic Peptides against TEM-1 Beta-Lactamases for Effective Antimicrobial Drug Development - A. Sowmiya; Santhoshkumar Jayakodi; K.A. Selvam; K. Sangeetha (Journal of Pure and Applied Microbiology, 2024)
Targeting the class A Beta lactamases Omega loop is an ideal way to combat drug resistance because of its significant role in the catalytic activity and deacylation process inhibition. Therefore, the molecular docking approach with computerized peptide-based in silico screening has been applied for the identification of inhibitors of TEM-type βLs. Among the subjected 105 peptides, Chrombacin (-47.8 KJ/mol), Gassericin A (-35.7 KJ/mol), Duramycin (-34.1 KJ/mol), Brevinin-1DYa (-34.0 KJ/mol), Amoebapore A (-31.2 KJ/mol), Mundticin ATO6 (-29.0 KJ/mol), Lactocyclicin Q (-26.3 KJ/mol), Cinnamycin (-25.9 KJ/mol showed highest binding energy. Among the peptides that showed the highest docking score Elafin, Cinnamycin, Duramycin interacted with Lys 73 of the α domain of catalytic residues of TEM-1 Beta lactamases, whereas Taromycin A, Gassericin A interacted with Lys 234 of the β domain, depicting a strong inhibition and also exhibited desirable physicochemical properties. Hence further in vitro examination of these cyclic peptides against the resistant strains is warranted to help design further novel inhibitors based on their scaffolds and also for the development of an effective drug combination regime.